Polymerizable thioureas as innovative reducing agents for self-cured and dual-cured dental materials. Issue 7 (July 2022) - Lamparth, Iris; Fässler, Pascal; Schnur, Thomas; Thetiot, Estelle; Lalevée, Jacques; Catel, Yohann
Abstract: Objective: To evaluate polymerizable acylthioureas as reducing agents in two-component dental materials. Methods: Acylthioureas 1 and 2 were synthesized and characterized by 1 H and 13 C NMR spectroscopy. Self-cured composites based on the redox initiator system cumene hydroperoxide/acylthiourea 1 or 2 /copper(II) acetylacetonate were formulated. Various amounts of cumene hydroperoxide, acylthiourea and copper(II) acetylacetonate were used. An equimolar cumene hydroperoxide/acylthiourea ratio was selected for each self-cured composite. The reactivity and the final double-bond conversions obtained with these two-component materials was assessed using RT-FTIR spectroscopy. The flexural strength and modulus were measured using a three-point bending setup, after storage of the specimens for 45 min at 37 °C (dry) and for 24 h in water at 37 °C. The working time of each composite was determined using an oscillating rheometer. Results: Acylthioureas 1 and 2 were synthesized in three to four steps. In combination with cumene hydroperoxide and copper(II) acetylacetonate, both prepared compounds were found to be effective reducing agents. The higher the amount of cumene hydroperoxide and acylthiourea in the self-cured composite, the higher the flexural modulus and the faster the polymerization (lower working times). Similarly, it was shown that increased copper(II) acetylacetonate amounts result in an acceleration of the curing as well as in an improvement of the mechanical properties. The self-cured composite containing 1.25 wt% of cumene hydroperoxide in the monomer mixture of the first paste and 2.00 wt% of acylthiourea 1 in the monomer mixture of the second one provided excellent mechanical properties as well as an optimal working time. Significance: Polymerizable acylthioureas can be used as reducing agents in two-component dental materials. Due to the presence of the methacrylate group, such structures should be efficiently incorporated into the network during polymerization and should not leach out of the composite after curing. As a result, such dental materials are not expected to exhibit bitterness properties. Highlights: Two polymerizable thioureas are synthesized and evaluated as reducing agents in self-cured dental materials. Polymerization kinetics of self-cured dental materials containing a polymerizable thiourea are investigated. Self-cured materials based on polymerizable thioureas exhibit excellent mechanical properties and a suitable working time.